Statistical study of acoustic emissions generated during the controlled deformation of migmatite specimens. (December 2017) - Vilhelm, J.; Rudajev, V.; Ponomarev, A.V.; Smirnov, V.B.; Lokajíček, T.
Abstract: Acoustic emissions generated during the mechanical loading of rocks provide information about the process of their fracturing and therefore have been used in the research of rock fracturing for many years. Laboratory loading experiments are used as a model of seismic processes in the field. Continuous loading is typically used to model natural tectonic processes, whereas stepwise loading can represent local stress field changes and evolution, similar to some features of rock fracturing due to water injection in the borehole with step-like injection history. During continuously increasing loading, acoustic impulses of a swarm character are generated. During stepped stress, however, the emission of acoustic signals generated has the character of an aftershock series and can be described by Omori's law for aftershock decay. The present work focuses on a detailed analysis of the seismoacoustic emissions generated in rock specimen during the stepwise increasing deformation during laboratory loading tests. A cylindrical specimen of migmatite was subjected to cyclical and stepwise loading with controlled deformation. The stepwise deformation increase was approximately 0.8 mStrain per one step and deformation rate was cca 8 mStrain/s. This sudden increase of deformation was accompanied by peak stress increase with duration of approximately 2 s. During load testing, seismoacoustic emissions were monitored and time series of acoustic impulses were recorded. It was found that the higher the level of stress, the longer the duration of aftershock sequence. Analysis of the autocorrelation functions of individual sequences showed significant changes in parameters at maximum specimen stress. An increase was found in the values of first autocorrelation coefficients, which can be used to assess the stability of the rock specimen.